Estimation and validation of InSAR-derived surface displacements at temperate raised peatlands - Alexis Hrysiewicz; Jennifer Williamson; Chris D. Evans; A. Jonay Jovani-Sancho; Nathan Callaghan; Justin Lyons; Jake White; Joanna Kowalska; Nina Menichino; Eoghan P. Holohan (Remote Sensing of Environment, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Mechanically induced histochemical and structural damage in the annulus fibrosus and cartilaginous endplate: a multi-colour immunofluorescence analysis - Jackie D. Zehr; Fasih Ahmad Rahman; Jack P. Callaghan; Joe Quadrilatero (Cell and Tissue Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Salvelinus namaycush spawning substratum attracts egg predators and opportunists through chemosensory cues - B. A. Wasylenko; D. T. Callaghan; P. J. Blanchfield; G. G. Pyle (Journal of Fish Biology, 2014)
Two separate field experiments were conducted in a series of small boreal lakes to test for the attraction of egg predators to lake trout Salvelinus namaycush spawning shoals and subsequently to determine whether chemosensory cues attract egg predators to these sites. In the first experiment, minnow traps set on spawning sites captured significantly more egg predators than those set on structurally similar non‐spawning sites. Captures of slimy sculpin Cottus cognatus , common shiner Luxilus cornutus , blacknose shiner Notropis heterolepis and virile crayfish Orconectes virilis were more than double on spawning sites relative to non‐spawning sites for the two study lakes. To test whether chemosensory cues could attract egg predators to S. namaycush spawning sites, paired minnow traps were placed on eight to 10 sites in each of the three study lakes; one trap contained visually concealed S. namaycush spawning substratum and the other with visually concealed non‐spawning substratum. Traps containing spawning substratum consistently captured more fish and had higher mean daily catches than those that contained non‐spawning substratum. The combined results demonstrate a greater prevalence of egg predators on S. namaycush spawning shoals that appears to be the result of chemosensory attraction to spawning substratum.

A geospatial assessment of the relationship between reef flat community calcium carbonate production and wave energy - S. M. Hamylton; A. Pescud; J. X. Leon; D. P. Callaghan (Coral Reefs, 2013)

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

Ecosystem responses to increased precipitation and permafrost decay in subarctic Sweden inferred from peat and lake sediments - U. KOKFELT; P. ROSÉN; K. SCHONING; T. R. CHRISTENSEN; J. FÖRSTER; J. KARLSSON; N. REUSS; M. RUNDGREN; T. V. CALLAGHAN; C. JONASSON; D. HAMMARLUND (Global Change Biology, 2009)
Recent accelerated decay of discontinuous permafrost at the Stordalen Mire in northern Sweden has been attributed to increased temperature and snow depth, and has caused expansion of wet minerotrophic areas leading to significant changes in carbon cycling in the mire. In order to track these changes through time and evaluate potential forcing mechanisms, this paper analyses a peat succession and a lake sediment sequence from within the mire, providing a record for the last 100 years, and compares these with monitored climate and active layer thickness data. The peat core was analysed for testate amoebae to reconstruct changes in peatland surface moisture conditions and water table fluctuations. The lake sediment core was analysed by near infrared spectroscopy to infer changes in the total organic carbon (TOC) concentration of the lake‐water, and changes in δ 13 C and C, N and δ 15 N to track changes in the dissolved inorganic carbon (DIC) pool and the influence of diagenetic effects on sediment organic matter, respectively. Results showed that major shifts towards increased peat surface moisture and TOC concentration of the lake‐water occurred around 1980, one to two decades earlier than a temperature driven increase in active layer thickness. Comparison with monitored temperature and precipitation from a nearby climate station indicates that this change in peat surface moisture is related to June–September (JJAS) precipitation and that the increase in lake‐water TOC concentration reflects an increase in total annual precipitation. A significant depletion in 13 C of sediment organic matter in the early 1980s probably reflects the effect of a single or a few consecutive years with anomalously high summer precipitation, resulting in elevated DIC content of the lake water, predominantly originating from increased export and subsequent respiration of organic carbon from the mire. Based on these results, it was not possible to link proxy data obtained on peat and lake‐sediment records directly to permafrost decay. Instead our data indicate that increased precipitation and anomalously high rainfall during summers had a significant impact on the mire and the adjacent lake ecosystem. We therefore propose that effects of increased precipitation should be considered when evaluating potential forcing mechanisms of recent changes in carbon cycling in the subarctic.

Microbial communities of Solanum tuberosum and magainin-producing transgenic lines - M. O’Callaghan; E. M. Gerard; N. W. Waipara; S. D. Young; T. R. Glare; P. J. Barrell; A. J. Conner (Plant and Soil, 2005)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Molecular and cellular targeting in the expression of foreign polypeptides in bacteria - J. -M. Clment; A. Charbit; C. Leclerc; P. Martineau; S. Muir; D. O'Callaghan; O. Popescu; S. Szmelcman; M. Hofnung (Antonie van Leeuwenhoek, 1992)